2018
DOI: 10.1186/s12909-018-1260-9
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and non-verbal communication skills including empathy during history taking of undergraduate medical students

Abstract: BackgroundVerbal and non-verbal aspects of communication as well as empathy are known to have an important impact on the medical encounter. The aim of the study was to analyze how well final year undergraduate medical students use skills of verbal and non-verbal communication during history-taking and whether these aspects of communication correlate with empathy and gender.MethodsDuring a three steps performance assessment simulating the first day of a resident 30 medical final year students took histories of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
68
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 55 publications
4
68
0
11
Order By: Relevance
“…On Running the Multi Variate Analysis for study variables with Statistical significance on logistic regression was seen for three variables-Exposure to External resources, Under graduation persued at same state and Age More than 35 Years.In this study Males out number females by Participation, Males contributed 55% and females were 45% only, But the Intelligence quotient or any other Unique technique among the gender perspective has not been applied in this study. But similar study by Vogel D, Meyer M et al, shows that female students showed Higher Scores for verbal communication compared to Male students while communicating with patients 3. Even the Empathy component in Nonverbal communication was also taken into study and Female students scored well than male students in the study by Vogel D, Meyer M et al…”
mentioning
confidence: 80%
“…On Running the Multi Variate Analysis for study variables with Statistical significance on logistic regression was seen for three variables-Exposure to External resources, Under graduation persued at same state and Age More than 35 Years.In this study Males out number females by Participation, Males contributed 55% and females were 45% only, But the Intelligence quotient or any other Unique technique among the gender perspective has not been applied in this study. But similar study by Vogel D, Meyer M et al, shows that female students showed Higher Scores for verbal communication compared to Male students while communicating with patients 3. Even the Empathy component in Nonverbal communication was also taken into study and Female students scored well than male students in the study by Vogel D, Meyer M et al…”
mentioning
confidence: 80%
“…Communication in medical encounters comprises verbal and non-verbal aspects. Non-verbal messages tend to override the verbal messages and as reported by Mehrabian and Ferris, the impact of the verbal communication represents only 7% from the total impact of communication [6,7]. On the other side, vocal communication has an impact of 38% and facial communication, 55% [6].…”
Section: Introductionmentioning
confidence: 91%
“…Communication in medical encounters comprises verbal and non-verbal aspects. Non-verbal messages tend to override the verbal messages and as reported by Mehrabian and Ferris, the impact of the verbal communication represents only 7% from the total impact of communication [5,6]. On the other side, vocal communication has an impact of 38% and facial communication, 55% [5].…”
Section: Introductionmentioning
confidence: 91%
“…There are several studies demonstrating comparable performance levels between ASP and SRP, but there is a cost-effectiveness advantage for SRP [16,17]. However, there are few studies that evaluate the most impactful part of the communication process, the non-verbal communication [5]. In this context, the aim of our study was to analyze whether and how well medical students from the Faculty of Medicine of Brest use skills of verbal and non-verbal communication in the 2 different approaches, SRP and ASP.…”
Section: Introductionmentioning
confidence: 99%